WEB TV Sebagai Media Alternatif Mengakses Informasi - Handayani, Sri (Jurnal The Messenger, 2010)
The Information Technologies are growing fast. One of them is Internet. There are various applications to share information offered in Internet. WebTV is one of them. WebTV is interactive television using Internet as its distribution media. WebTV can be watched all the time, both delay or direct broadcasting.There are some main benefits of WebTV compared with common television are: there are no competition in getting frequency, the consumers are not limited by time to watch their preferred programs, there is an interaction in internet in using such services as e-mail, chat, e-commerce, e-government, e-education, digital trend influences the compound of television and internet, One of the strategies used in television industry is increasing the brand image.